(untitled) (Acta Scientiarum. Animal Sciences, 2017)
The high cost of nitrogen fertilizers increases the expenses in pasture-based animal production. The inoculation with plant growth-promoting bacteria is an alternative to reduce the costs. This study evaluated the forage yield of Coastcross-1 pastures inoculated with Azospirillum brasilense, fertilized with different levels of nitrogen and subjected to cuts. The experiment was a factorial randomized block design with three replications. The factors were the inoculation (without inoculation, inoculated only at planting and reinoculated in the second year), levels of nitrogen (0, 100 and 200 kg ha-1 year-1 N) and seasons (spring, summer, fall and winter) when cuts were made. Forage yield, forage accumulation rate, botanical and structural pasture composition were evaluated. Forage yield without nitrogen fertilizer in pastures was in the first year 9.1, 11.7 and 11.7 t ha-1 DM, and in the second year 8.6, 11.2 and 11.5 t ha-1 DM, for the factor inoculation, respectively. The forage yield rises with inoculation at pasture planting, without nitrogen fertilization. Reinoculation is not necessary.